A New Score to Predict the Risk of Hearing Impairment After Microvascular Decompression for Hemifacial Spasm. Issue 5 (November 2017) - El Damaty, Ahmed; Rosenstengel, Christian; Matthes, Marc; Baldauf, Joerg; Dziemba, Oliver; Hosemann, Werner; Schroeder, Henry W S
Abstract : BACKGROUND: : Intraoperative monitoring of brainstem auditory evoked potentials (BAEPs) has been implemented to reduce the risk of hearing impairment during microvascular decompression for hemifacial spasm. OBJECTIVE: : To evaluate intraoperative monitoring of BAEPs during microvascular decompression in patients with hemifacial spasm for predicting the risk of hearing impairment after surgery. METHODS: : This prospective study included 100 patients. BAEPs were recorded for all patients. We established a scoring system for the changes in wave I amplitude, I‐III interpeak latency, and wave V amplitude and latency. For each change, total points were calculated, and a score out of 6 was assigned to every patient. We classified the patients based on the points scored into 3 risk groups: low‐risk (0‐3), medium‐risk (4‐5), and high‐risk (6). Further, the correlation between the score and the hearing outcome was evaluated to detect the incidence and degree of hearing impairment. RESULTS: : Eighty‐seven patients scored 0 to 3, 10 scored 4 to 5, and 3 scored 6. The degree of hearing impairment was proportionate to the score recorded at the end of surgery, and patients in the low‐risk group showed no impairment; medium‐risk group, deterioration of maximum 2 grades according to World Health Organization classification of hearing impairment; and high‐risk group, deterioration of 3 to 4 grades. CONCLUSION: : Intraoperative monitoring of BAEPs evaluated through our scoring system was valuable in predicting hearing impairment after surgery.